Advancing psychiatric pharmacogenomics using drug development paradigms. (October 2017) - Smith, Ryan M
Drugs used to treat psychiatric disorders, even when taken as directed, fail to provide adequate relief for a sizeable proportion of patients. Despite our advancements in understanding human genetics and development of high-throughput tools to probe variation, pharmacogenomics has yielded marginal ability to predict drug response for psychiatric disorders. Here, I review the current pharmacogenomics paradigm, identifying opportunities to incorporate drug development strategies designed to increase the probability of delivering a successful molecule to the clinic. This includes using in-depth pharmacokinetic profiles, clear measures of target engagement and target-specific pharmacodynamic responses orthogonal to clinical response. The complex pharmacological profiles psychiatric drugs require re-examination of simplified clinical response-oriented pharmacogenetic hypotheses, in favor of a more complete patient profile.